The potential conflict of interest associated with the management of Rosa rubiginos L. (Rosehip) in South Africa - Westwood, Timothy (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2021)
Rosa rubiginosa L. is a category 1b invasive plant species in South Africa and must be controlled according to NEM:BA. However, R. rubiginosa has the potential to provide economic benefit in South Africa due to the expanding market for the shrubs fruit, rosehips. The shrub is not permitted to be cultivated in South Africa due to legislation, limiting the economic potential as the rosehips are only able to be collected from wild R. rubiginosa shrubs. In order to expand the rosehip market in South Africa a downgrade or removal of R. rubiginosa from the invasive species list would be required, as wild harvest is limited. This study aims to assess the benefits and cost associated with R. rubiginosa in order to determine whether the legislation should be altered allowing for the cultivation of the shrub in South Africa. Due to the limited literature surrounding R. rubiginosa three different questionnaires and a case study were used in order to assess the benefits and negatives associated with the shrub. Experts in the field of invasion biology were surveyed to bridge the gap in the R. rubiginosa literature. Landowners, where the shrub is abundant, were surveyed to determine the negative impacts of R. rubiginosa. Rosehip companies were surveyed in order to determine the current size and potential of the R. rubiginosa (rosehip) market. The case study looked at how a rosehip company would benefit if R. rubiginosa was allowed to be cultivated in South Africa. The study found R. rubiginosa to have great economic potential and market growth, with very little negative economic impact. The case study showed that one rosehip company would grow from 1500 tons of raw rosehip to 20 000 tons if cultivation was allowed, resulting in a growth in turnover from R57 million to R760 million ($1=R14.8). The findings in the study show that R. rubiginosa does not significantly affect landowners where it is abundant. Therefore, it is suggested that a change to the legislation should be considered allowing for the cultivation of R. rubiginosa should be implemented.
Keywords: Invasive plants -- South Africa; Biological invasions -- Economic aspects; Rose hips -- Economic aspects -- South Africa; Roses -- South Africa; Rose culture -- Economic aspects -- South Africa